Modification and optimization of an established prognostic score after re-irradiation of recurrent glioma - Kessel, Kerstin A. (PLoS One, 2017)
INTRODUCTION: For about 30 years, researchers developed prognostic scores and searched for prognostic factors to predict outcomes for cancer patients. The “Combs Prognostic Score” for re-irradiation in recurrent glioma was recently validated and results showed that the score is a significant (p < .001) and reliable predictor for patients undergoing re-irradiation (re-RT). We sought to enhance the score and generated a novel scoring approach, taking into account the information on resection of recurrent tumors, KPS, and tumor volume. PATIENTS AND METHODS: The prognostic score was generated based on 209 patients treated between 2002 and 2016 for recurrent glioma at the department of radiation oncology at the Klinikum rechts der Isar, Munich. To further enhance the previously validated Combs Prognostic Score, which uses the prognostic factors primary histology, time between primary RT and re-RT, and age, we added KPS, tumor volume (PTV) and re-resection into the scoring scheme. RESULTS: The median follow-up time was 3.5 months. 67.5% were WHO IV gliomas with a median OS after re-RT of 7.9 months, 17.7% were WHO III gliomas with an OS of 11.3 months and 14.8% were WHO I/II gliomas with an OS of 14.7 months. Multivariate analyses confirmed the prognostic factors KPS (p < .001) and showed a tendency to significance for tumor volume (p = .067) and re-resection (p = .064). The new prognostic score demonstrated a high significance (p < .001). CONCLUSION: The “New Combs Prognostics Score” is a significant and useful tool to predict the overall effect of re-RT in patients with recurrence gliomas. This modified score offers an even better way to classify patients in clinical routine and prospective clinical trials investigating re-irradiation.